Global, regional, and national disease burden of lymphoma and leukemia attributable to high body mass index: from 1990 to 2021 - Zhou, Li; Shan, Dongyong; Zhang, Yingzhe; Li, Jiwei; Deng, RenFang (Frontiers in Nutrition, 2025)
BackgroundLymphoma and leukemia were the most common hematological malignancies worldwide. Metabolic factors, such as high body mass index, are potential risk factors for various cancers. This study aimed to analyze the disease burden and the incidence trend of non-Hodgkin and acute leukemia attributable to high BMI around the world from 1990 to 2021.MethodsUsing the data released by the Global Burden of Disease study 2021 (GBD 2021), we analyze the disease burden of non-Hodgkin lymphoma and acute leukemia attributable to high BMI from 1990 to 2021 via morbidity, death, disability-adjusted life years (DALY), and predict the obesity-related death trend in for the next 20 years (2022–2046).ResultsThe death cases of non-Hodgkin lymphoma, acute myeloid leukemia and acute lymphoid leukemia attributable to BMI in 2021 were 12,796, 11,947 and 4,116 respectively, with an increase of 153,9, 169.9, and 92.6% compared with 1990. The age-standardized mortality rate (ASMR) in 2021 attributable to BMI grew from 0.13/100,00, 0.11/100,000 and 0.05/100,000 in 1990 to 0.15/100,00, 0.14/100,00 and 0.05/100,000 in 2021. In 2021, the number of deaths cases and DALYs case were generally higher in male population and older population. The prediction of the neural network model showed that the incidence and death of the disease would remain high and rise in the next 25 years.ConclusionHigh BMI has become a risk factor for leukemia and lymphoma and threatened public health globally. We should pay more attention to the role of metabolic factors and made more proactive and effective strategies.